2017
DOI: 10.1155/2017/1367683
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wheel Eccentricity on Vertical Vibration of Suspended Monorail Vehicle: Experiment and Simulation

Abstract: This paper investigates the influence of wheel eccentricity on vertical vibration of suspended monorail vehicle based on experiment and simulation. Two sets of tests are conducted in the first Chinese suspended monorail, and the tested acceleration is analyzed and exhibited. A multibody dynamic model of the suspended monorail vehicle is established to simulate the vertical vibration of car body excited by wheel eccentricity. The results show that there are three factors which may cause an abnormal vibration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The excitation frequency of the wheel eccentricity is generally less than 10 Hz for an ordinary-speed vehicle, which can easily transmit to the car body and lead to a decrease in ride comfort. Lv et al [43] and Jiang et al [44] reported the influence of wheel eccentricity on the vertical vibration of suspended monorail vehicles and straddle monorail vehicles, respectively. The abnormal vibration of the two types of monorail vehicle was mainly caused by wheel eccentricity, although they were equipped with a solid tire rather than a steel wheel.…”
Section: Effects Of Wheel Polygonisation On Vibrationmentioning
confidence: 99%
“…The excitation frequency of the wheel eccentricity is generally less than 10 Hz for an ordinary-speed vehicle, which can easily transmit to the car body and lead to a decrease in ride comfort. Lv et al [43] and Jiang et al [44] reported the influence of wheel eccentricity on the vertical vibration of suspended monorail vehicles and straddle monorail vehicles, respectively. The abnormal vibration of the two types of monorail vehicle was mainly caused by wheel eccentricity, although they were equipped with a solid tire rather than a steel wheel.…”
Section: Effects Of Wheel Polygonisation On Vibrationmentioning
confidence: 99%
“…e MI-7008D portable data acquisition analyzer and two three-axis accelerometers were used to measure the acceleration [24,28]. e parameters of the double-bogie vehicle before the optimization are given in Table 5.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Wheel out-of-roundness (OOR) widely occurs in all kinds of railway vehicle, such as locomotive, [1][2][3][4][5] highspeed train, [6][7][8][9][10] metro train, [11][12][13][14][15] as well as monorail. 16,17 The wheel OOR shows the fluctuation of wheel radius along the circumference. The radial run-out is generally less than 1 mm and the wavelength of wheel OOR ranges from 100 mm to approximately one wheel circumference, which can cause severe wheel-rail dynamic interaction, especially for high-order wheel OOR.…”
Section: Introductionmentioning
confidence: 99%